2022
DOI: 10.3390/ijms23020659
|View full text |Cite
|
Sign up to set email alerts
|

Placental Dysfunction in Assisted Reproductive Pregnancies: Perinatal, Neonatal and Adult Life Outcomes

Abstract: Obstetric and newborn outcomes of assisted reproductive technology (ART) pregnancies are associated with significative prevalence of maternal and neonatal adverse health conditions, such as cardiovascular and metabolic diseases. These data are interpreted as anomalies in placentation involving a dysregulation of several molecular factors and pathways. It is not clear which extent of the observed placental alterations are the result of ART and which originate from infertility itself. These two aspects probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…Placenta not only regulates the development of the fetus, but also dysplasia of placenta will lead to poor maternal and perinatal outcomes as well as long-term health risks later in life, including neurodevelopmental disorders, tumors, and adult metabolic syndrome ( 10 , 11 ). There is sufficient evidence that ART may be related to changes in placental morphology and structure, growth dynamics, imprinted and non imprinted genes, and other aspects that regulate placental formation ( 12 , 13 ). Several studies have shown that the incidence of placenta previa in ART is significantly higher than in natural pregnancy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Placenta not only regulates the development of the fetus, but also dysplasia of placenta will lead to poor maternal and perinatal outcomes as well as long-term health risks later in life, including neurodevelopmental disorders, tumors, and adult metabolic syndrome ( 10 , 11 ). There is sufficient evidence that ART may be related to changes in placental morphology and structure, growth dynamics, imprinted and non imprinted genes, and other aspects that regulate placental formation ( 12 , 13 ). Several studies have shown that the incidence of placenta previa in ART is significantly higher than in natural pregnancy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Для виконання плацентою своїх функцій принциповою умовою є достатня її маса. Крім відносності достатності маси (її надлишкового резерву), слід враховувати, що йдеться насамперед про масу функціонуючих клітин, адже органна маса (як і об'єм) є величиною інтегральною (а значить орієнтовною), яка включає в плаценті також екстрацелюлярний матрикс, фібриноїд, плодову кров та залишки материнської крові, кальцифікати, можливі некротичні ділянки, кісти тощо [17][18][19][20]. Значущість цих структурних компонентів у функціональному аспекті нерівнозначна.…”
Section: акушерствоunclassified
“…However, if IVF and PRS-ES are undertaken solely for the purposes of PRS-ES, the future person could, in one sense, be harmed by PRS if that procedure exposes him or her to avoidable risks. For example, PGT has been associated with certain uncommon side effects in pregnancy ( Makhijani et al , 2021 ), which may have long-term consequences ( Manna et al , 2022 ). Multiple medical conditions also appear to be more prevalent in ART-conceived individuals compared to their naturally conceived peers ( Chen and Heilbronn, 2017 ; von Wolff and Haaf, 2020 ; Luke, 2021 ).…”
Section: Ethical and Social Implicationsmentioning
confidence: 99%